2020
DOI: 10.3390/pr8121684
|View full text |Cite
|
Sign up to set email alerts
|

Flow and Diffusion Characteristics of Typical Halon Extinguishing Agent Substitute under Different Release Pressures

Abstract: To provide guidance towards reducing the weight of the HFC-125 storage vessel by reducing the release pressure and to reveal the effects of release pressure on the extinguishing efficiency of HFC-125, we investigated the flow and diffusion characteristics of HFC-125 under six release pressures in the present study. The influence of release pressure on the degree of superheat, injection duration, pressure loss, jet angle, and concentration distribution were analyzed. Results show that the degree of superheat an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Huynh et al [18] describes a green and facile method for the preparation of multibranched gold nanoparticles using hydroquinone as a reducing agent and chitosan as a stabilizer, through ultrasound irradiation to improve the multibranched shape and stability. To provide guidance towards reducing the weight of the HFC-125 storage vessel by reducing the release pressure and to reveal the effects of release pressure on the extinguishing efficiency of HFC-125, Jin et al [19] investigate the flow and diffusion characteristics of HFC-125 under six release pressures in the present study. Results show that the degree of superheat and the injection duration both decreased with the release pressure.…”
Section: Other Issuesmentioning
confidence: 99%
“…Huynh et al [18] describes a green and facile method for the preparation of multibranched gold nanoparticles using hydroquinone as a reducing agent and chitosan as a stabilizer, through ultrasound irradiation to improve the multibranched shape and stability. To provide guidance towards reducing the weight of the HFC-125 storage vessel by reducing the release pressure and to reveal the effects of release pressure on the extinguishing efficiency of HFC-125, Jin et al [19] investigate the flow and diffusion characteristics of HFC-125 under six release pressures in the present study. Results show that the degree of superheat and the injection duration both decreased with the release pressure.…”
Section: Other Issuesmentioning
confidence: 99%
“…In this stage, the liquid in the bottom moves from the bottle to the pipe. At the second stage, the dissolved nitrogen releases from the liquid [13][14][15][16][17][18][19][20]. The released nitrogen forms bubbles, and increases the gas volume fraction of the outflow.…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the bottle condition on the discharge process was studied by Li Q. et al [13,14]. It was found that as the initial bottle pressure increased, the discharge time decreased exponentially and nitrogen bubbles occurred earlier.…”
Section: Introductionmentioning
confidence: 99%